Recent Advances in Engineered Nanoparticles for RNAi-Mediated Crop Protection Against Insect Pests - Pugsley, Charlotte E.; Isaac, R. E.; Warren, Nicholas J.; Cayre, Olivier J. (Frontiers in Agronomy, 2021)
Since the discovery of RNA interference (RNAi) in the nematode worm Caenorhabditis elegans in 1998 by Fire and Mello et al., strides have been made in exploiting RNAi for therapeutic applications and more recently for highly selective insect pest control. Although triggering mRNA degradation in insects through RNAi offers significant opportunities in crop protection, the application of environmental naked dsRNA is often ineffective in eliciting a RNAi response that results in pest lethality. There are many possible reasons for the failed or weak induction of RNAi, with predominant causes being the degradation of dsRNA in the formulated pesticide, in the field or in the insect once ingested, poor cuticular and oral uptake of the nucleic acid and sometimes the lack of an innate strong systemic RNAi response. Therefore, in the last 10 years significant research effort has focused on developing methods for the protection and delivery of environmental dsRNA to enable RNAi-induced insect control. This review focuses on the design and synthesis of vectors (vehicles that are capable of carrying and protecting dsRNA) that successfully enhance mRNA degradation via the RNAi machinery. The majority of solutions exploit the ability of charged polymers, both synthetic and natural, to complex with dsRNA, but alternative nanocarriers such as clay nanosheets and liposomal vesicles have also been developed, see Fig. 1. The various challenges of dsRNA delivery and the obstacles in the development of well-designed nanoparticles that act to protect the nucleic acid are highlighted. In addition, future research directions for improving the efficacy of RNA-mediated crop protection are anticipated with inspiration taken from polymeric architectures constructed for RNA-based therapeutic applications.